Identification of Vibrio ponticus as a bacterial pathogen of coral trout Plectropomus leopardus - Gai, Chunlei; Liu, Jie; Zheng, Xurui; Xu, La; Ye, Haibin (Frontiers in Cellular and Infection Microbiology, 2022)
Vibrio ponticus is a vital pathogen with potential danger for aquaculture animals. Yet V. ponticus pathogenic to the coral trout Plectropomus leopardus is still unknown. In this study, a virulent bacterial strain, temporarily named DX2, was isolated from diseased coral trout suffering liver necrosis with cell vacuolar degeneration, and was identified molecularly and phenotypically as V. ponticus. Besides, the DX2 isolate showed an LD50 value of 6.64×105 CFU mL-1, developed multiple resistances to cephalosporins, macrolides, penicillins, peptides, and sulfonamides antimicrobials, and was highly susceptible to doxycycline and florfenicol in aquaculture use. To the best of our knowledge, this is the first report of the pathogenicity of V. ponticus to the coral trout, and the findings provide a reference for the control of pathogenic V. ponticus in the coral trout.